2023
DOI: 10.5582/bst.2022.01476
|View full text |Cite
|
Sign up to set email alerts
|

Detecting latent tuberculosis infection with a breath test using mass spectrometer: A pilot cross-sectional study

Abstract: It is estimated that Mycobacterium tuberculosis (M.tb) infected a quarter of the world's population (1). Latent tuberculosis infection (LTBI) constitutes a broad spectrum of infection states that differ by the degree of pathogen replication, host immune response, and inflammation (2). Approximately 5-10% of those with LTBI will progress to active tuberculosis (ATB) (3). WHO recommends immunodiagnostic tests for LTBI detection, either a tuberculin skin test (TST) or interferon-gamma (IFN-γ) release assays (IGRA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
0
0
Order By: Relevance
“…While a small cohort size, the study provides insight as TB is a leading cause of childhood mortality, and adults and children have different breath profiles. Another study (n = 435) utilized breath analysis to distinguish latent tuberculosis infection (LTBI) from controls, the latter comprising active TB (ATB) and healthy controls (Fu et al, 2023 ). The model showed that breath VOCs could distinguish LTBI from controls with 80.0% sensitivity and 80.8% specificity.…”
Section: Infectious Diseasesmentioning
confidence: 99%
“…While a small cohort size, the study provides insight as TB is a leading cause of childhood mortality, and adults and children have different breath profiles. Another study (n = 435) utilized breath analysis to distinguish latent tuberculosis infection (LTBI) from controls, the latter comprising active TB (ATB) and healthy controls (Fu et al, 2023 ). The model showed that breath VOCs could distinguish LTBI from controls with 80.0% sensitivity and 80.8% specificity.…”
Section: Infectious Diseasesmentioning
confidence: 99%
“…In this study, for the first time, we investigated the potential of breath analysis to differentiate among PTB, NTM-PD, OPD and healthy controls (HC), and identified 22 potential VOC biomarkers associated with PTB and NTM-PD, extending our previous PTB breath detection research [17] [18]. Moreover, by employing our self-developed on-line mass spectrometer for human breath-the highpressure photon ionisation time-of-flight mass spectrometry (HPPI-TOF-MS) [20], we built a rapid and simple online breath analysis and modeling method for MPD screening and diagnosis.…”
Section: Introductionmentioning
confidence: 97%
“…Recently, Beccaria et al used GC×GC-MS to analyse exhaled VOCs of PTB patients and suspected PTB patients / other controls in South Africa / Haiti, achieving high sensitivity and specificity based on 23 / 22 feature VOCs [14] [15], respectively. Other recent studies have focused on pediatric [16] and adult PTB diagnosis [17] and TB infection (TBI) screening [18]. In addition to the above TB VOC-identified studies, sensor-based breath analyses have also shown promise in detecting PTB without biomarkers revealed [7].…”
Section: Introductionmentioning
confidence: 99%
“…A standardized workflow has been established using HPPI-TOF-MS for the collection, detection, and data processing of exhaled VOCs, and has validated the feasibility of this technology in detecting diseases such as breast cancer [ 24 ], lung cancer [ 25 ], esophageal cancer [ 26 ], tuberculosis [ 27 ], and Covid-19 [ 28 ]. We aimed to integrate breath-omics, ultrasound radiomics, and clinical features to construct a multi-omics machine learning model, to develop a more accurate, objective, and automated non-invasive diagnostic tool for breast cancer.…”
Section: Introductionmentioning
confidence: 99%